Multi-band MIMO Antenna with Square-Ring Slots for 5G Services - Syaza Ibra Harlin; Firdaus Nursal; Amelia Yolanda (International Journal of Wireless And Multimedia Communications, 2025)
Mobile communications technology is evolving rapidly with the introduction of 5G networks, which offer high speeds, low latency, and greater network capacity. To support these services, antennas that can operate optimally in a wide frequency range are required. The objective of this research is to design and analyze a multi-band square-ring slot MIMO antenna operating at frequencies of 2.6 GHz, 3.6 GHz, and 5.25 GHz. The antenna design is performed using CST Studio Suite 2019 software, and the simulation results are compared with the measurement results after fabrication. The antenna structure utilizes a microstrip design with an FR-4 substrate, optimizing parameters such as slot dimensions, feed line positioning, and element spacing to achieve the desired performance. The results show that the designed antenna has a return loss of < -10 dB, VSWR values in the acceptable range (1 ≤ VSWR ≤ 2), mutual coupling isolation below -20 dB, and ECC < 0.05, indicating good MIMO performance. In addition, the antenna exhibits an omnidirectional radiation pattern, a gain of more than 4 dBi with a maximum of 5.25 dBi at 2.6 GHz, and a wide bandwidth suitable for 5G applications. Although there are differences between simulated and measured results due to environmental factors and manufacturing tolerances, the antenna performance remains within acceptable limits. This research proves that the multi-band MIMO design with a square-ring slot can be an effective and practical solution to enhance 5G service quality, offering advantages for future wireless communication systems.